Gender differences in trunk and pelvic kinematics during prolonged ergometer rowing in adolescents - Ng, Leo; Campbell, Amity; Burnett, A.; O'Sullivan, Peter (International Society of Biomechanics, 2013)
The trunk and pelvis kinematics of 20 healthy male and female adolescent rowers were recorded during an ergometer trial using an electromagnetic tracking system (Fastrak). The kinematics of each drive phase were collected during the 1st and 20th minute, respectively. The mean and range of the kinematics, stroke rate and stroke length were compared between genders and over time. Male rowers postured their pelvis with more posterior tilt and their thoracic spine in more flexion than female rowers (P < .05). Both genders postured their pelvis in more posterior pelvic rotation and upper trunk in more flexion over time. Male rowers were found to have a significantly shorter drive phase than female rowers (P = .001). Differences in trunk and pelvic kinematics between adolescent male and female rowers suggest potentially various mechanisms for biomechanical stress. Assessment and training of rowers should take gender differences into consideration.